The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11269-015-0989-8
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Monitoring Network Design Using GIS and Multicriteria Analysis

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media Dordrecht. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Also, other researchers have used fuzzy clustering (Moradi Dashtpagerdi et al 2013) for flood spreading, spatial optimization techniques (Durga Rao 2014) for planning groundwater supply scheme, distributed hydrogeological budget (Mazza et al 2014) for evaluating the available regional groundwater resources, multi-criteria analysis (Esquivel et al 2015) for groundwater level monitoring, an optimization-simulation approach (Zekri et al 2015) for groundwater abstraction under recharge uncertainty, and spatial multi-criteria evaluation (Chezgi et al 2015) for underground dam site selection.…”
Section: Introductionmentioning
confidence: 99%
“…Also, other researchers have used fuzzy clustering (Moradi Dashtpagerdi et al 2013) for flood spreading, spatial optimization techniques (Durga Rao 2014) for planning groundwater supply scheme, distributed hydrogeological budget (Mazza et al 2014) for evaluating the available regional groundwater resources, multi-criteria analysis (Esquivel et al 2015) for groundwater level monitoring, an optimization-simulation approach (Zekri et al 2015) for groundwater abstraction under recharge uncertainty, and spatial multi-criteria evaluation (Chezgi et al 2015) for underground dam site selection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding the use of GIS-based MCDA in finding an optimal site for a wind farm were conducted by Szurek et al (2014) Several researchers have used GIS-based MCDA for disaster, e.g., flood, risk management and mitigation (Papaioannou et al 2015;Xiao et al 2016;Fernandez et al 2016;Rahmati et al 2016;Pourghasemi et al 2014, Dragicevic et al 2015, landslide susceptibility mapping (Erener et al 2017) Groundwater is also an interesting study object for several researchers. Using GISbased MCDA, Sahoo et al (2015) and Saidi et al (2017) explored groundwater prospects, Esquivel et al (2015) and Sing and Katpatal 2017 This paper is closely related to two of my earlier papers. The factor investigated in this study was taken from a public preference factor identified using Web-GIS application in the first paper , while the use of the Web-GIS application for collecting AHP judgements was based on another research study conducted in the same year ).…”
Section: R a F Tmentioning
confidence: 80%
“…Such strategic, nested sampling, would be best accomplished with supply wells rather than purpose installed monitoring wells (that, with low use, would be prone to loss, vandalism etc.). It is recommended, if the framework approach is being used in this way, with a significant leaning towards providing a basis for spatial surveillance monitoring, that spatial statistical analysis is later employed using monitored data collected over the first 1 to 6 years (hence including 2 detailed spatial snapshots) to allow further optimisation of core network points selected and their appropriateness for temporal and spatial monitoring and delivery of monitoring objectives (Esquivel et al, 2015;Kollat et al, 2011;SOGW, 2013).…”
Section: Potential Implementation (Steps 7 -9)mentioning
confidence: 99%
“…It is intended to be relevant to both developing and developed world contexts, albeit motivated by the apparent needs of the former. Our framework does not purport to be a statistical-based methodology to optimise network point assignment (Esquivel et al, 2015;Kollat et al, 2011;Qin et al, 2016). Rather, it seeks to offer a straightforward, uncomplicated, step-wise framework for network establishment that is versatile and easy-to-use.…”
Section: Introductionmentioning
confidence: 99%